Herman de Liagre Böhl, Amsterdammer in de polder. Han Lammers (1931-2000) - Wijfjes, Huub (BMGN - Low Countries Historical Review, 2016)
Herman de Liagre Böhl, Amsterdammer in de polder. Han Lammers (1931-2000) (Amsterdam: Prometheus/Bert Bakker, 2015, 309 pp., isbn 978 90 351 4312 8).